Introduction: globalization and change in India - Mukherji, Rahul (India review, 2019)
This series of papers on Globalization, Institutional Change, and Politics of reforms in India highlights some of the key characteristics of institutional change and globalization in India. This special issue points in the direction of three important conjectures on globalization and change by bringing together a few key aspects of the process of institutional change and engagement with the global in India. First, India’s liberal democracy has embraced globalization and globally influenced institutional change in an embedded liberal way. Second, this is a saga of gradual and largely endogenous change. India is deeply affected by the demonstration effect of global best practices but builds rather more after its own internal consensus. Finally, even though India is not a classic developmental state, the state is an important factor in promoting change.
Gesehen am 08.07.2019